Legal Protection of Building Tenants in the Execution of Land Rights - ANGGARINI, Komang Desy; SUWITRA, I Made; WESNA, Putu Ayu Sriasih (Journal of Political And Legal Sovereignty, 2025)
Purpose:The purpose of this study is to find a legal protection model for tenants of buildings whose land is used as collateral by the landowner. Therefore, the relevant issues to be discussed are legal protection for tenants of buildings whose land is used as collateral by the landowner and the function of good faith in protecting tenants of buildings whose land is subject to foreclosure.Methodology:The research method used is normative legal research with a legislative approach, conceptual approach, and case study. The analysis of legal materials used is analysis with interpretation and content techniques.Findings:The results of the study indicate that the principle of horizontal separation provides a basis for separating building rights from land rights, thereby ensuring that tenants retain a strong legal position. In addition, the principle of good faith is a key consideration in protecting tenants' rights, as emphasised in SEMA No. 4 of 2014, which stipulates that tenants' rights shall be respected throughout the term of the leaseImplication:This study recommends strengthening regulations, transparency regarding the status of leased properties, and legal education for the public to create legal certainty and fairness in the practice of leasing buildings on land that is used as collateral for mortgage rights.